Gomułka - Slightly Autistic? - Rokicki, Konrad (Sensus Historiae, 2021)
Władysław Gomułka, a long-standing leader of the Polish Communist Party (first of the Polish Workers’ Party and later of Polish United Workers’ Party), was a man of strong character who commanded substantial respect and authority in his milieu. At the same time, he was hard to get along with, as he tried to control everything on his own. His governed apodictically, confident about his infallibility. People found it hard to change his mind and increasingly easier to trigger a bout of his anger. About this we can be quite certain. Why, then, did Gomułka behave the way he did? Was it only due to his character? The author proposes a new interpretation, that is arguably his Asperger syndrome.